Do bisphosphonates and RANKL inhibitors alter the progression of coronary artery calcification? A systematic review - Kanika Chaudhri; Sonali R Gnanenthiran; Samantha Louise Saunders; Nathan Scott McOrist; Grant Shalaby; Karen Gladysz (BMJ Open, 2024)
Objectives To determine whether bisphosphonates and NF-κB ligand (RANKL) inhibitors delay coronary artery calcification (CAC).Design A systematic review was conducted.Data sources MEDLINE, EMBASE and CENTRAL.Eligibility criteria Longitudinal studies investigating CAC progression in adults (>18 years) taking either a bisphosphonate or denosumab compared with those who did not.Data extraction and synthesis Study and participant characteristics, and primary outcome (∆CAC from baseline to follow-up) were extracted. The Risk Of Bias In Non-Randomised Studies-of Interventions (ROBINS-I) and Risk-of-Bias Tool for Randomised Trials (RoB2) tools were used to assess the risk of bias for observational and randomised controlled trials (RCTs), respectively. Outcome measures were reported.Results Four observational studies and one RCT (n=377) were included. Three studies solely reported the effect of bisphosphonates on ∆CAC; one study (n=56) demonstrated a statistically significant CAC reduction in the intervention group (−372 mm3/year) compared with control (+159 mm3/year) (p<0.01). One study (n=14) demonstrated a difference in ∆CAC between intervention (+880 mm3/year) versus control (+2220 mm3/year), however, no p value comparing groups was reported. One study (n=115) found no statistically significant difference between intervention and control.One study (n=42) exclusively investigated the effect of RANKL on ∆CAC; there was a statistically significant reduction in CAC at 6-month follow-up between intervention (−133±124 modified Agatston unit (AU)) and control (+188±72 modified AU), p=0.03.One study (n=150) compared both bisphosphonates and denosumab to control and found no statistically significant difference between either intervention group and control over 24 months. Meta-analysis was not performed due to limited, heterogeneous studies.Conclusions There is insufficient evidence supporting the correlation between bisphosphonate or RANKL inhibitor use and CAC progression. Further research is warranted.